50‐2: Development of New Head‐Up Display System Utilizing RGBW LCD and Local Dimming Backlight. Issue 1 (May 2016) - Sako, Kazuhiko; Takasaki, Naoyuki; Aoki, Shigenori; Yata, Tatsuya; Harada, Tsutomu
Abstract : We have developed a prototype of a head‐up display system using transmissive LCD with direct‐lit backlight type 2D local dimming and RGBW technology. We confirmed that the postcard effect, which is a phenomenon where the entire projection area including the noninformation area is slightly illuminated, was virtually eliminated. We also achieved higher white luminance and lower backlightpower.